Method for manufacturing a polarizing plate with a retardation layer

JP7633782B2Active Publication Date: 2025-02-20NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020148150
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-03
Publication Date
2025-02-20
Estimated Expiration
2040-09-03

Smart Images

  • Figure 0007633782000003
    Figure 0007633782000003
  • Figure 0007633782000004
    Figure 0007633782000004
  • Figure 0007633782000001
    Figure 0007633782000001
Patent Text Reader

Abstract

To provide a simple and efficient manufacturing method of a polarizing plate having a phase difference layer in which warpage is suppressed.SOLUTION: A manufacturing method of a polarizing plate 100 having a phase difference layer includes: laminating a polarizing plate 10 and a phase difference layer 20 via an active energy ray curing adhesive while performing roll conveyance under environment in which a saturated steam amount is 10.2 g / m3 or less, and obtaining a polarizing plate having a phase difference layer; performing humidification treatment such that weight per unit volume increases by 0.2% or more under environment of 18°C to 34°C and 60%RH to 90%RH while performing roll conveyance of the polarizing plate having the phase difference layer; and rewinding the polarizing plate having the phase difference layer after humidification treatment in a roll and storing it in a roll state for six hours or longer. The total thickness of the polarizing plate having the phase difference layer is 80 μm or less, and a ratio of the thickness of the polarizing plate to the thickness of the phase difference layer (polarizing plate / phase difference layer) is 5 or larger.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polarizing plate with a retardation layer. [Background technology]

[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), are rapidly becoming widespread. A polarizing plate and a retardation plate are typically used in image display devices. In practice, a retardation layer-attached polarizing plate in which a polarizing plate and a retardation plate are integrated is widely used (e.g., Patent Document 1). In recent years, the possibility of curving, bending, folding, and rolling up image display devices has been studied. As a retardation layer-attached polarizing plate to be used in such image display devices, a thin retardation layer-attached polarizing plate is desired. However, a thin retardation layer-attached polarizing plate has a problem in that it is prone to warping. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and a main object of the present invention is to provide a simple and efficient method for producing a polarizing plate with a retardation layer in which warping is suppressed. [Means for solving the problem]

[0005] According to an embodiment of the present invention, there is provided a method for producing a polarizing plate with a retardation layer, the polarizing plate including a polarizer and a protective layer on at least one of the polarizers, and a retardation layer. ,water Steam volume is 10.2g / m 3The method includes laminating a polarizing plate and a retardation layer via an active energy ray curable adhesive while transporting the polarizing plate with a roll under the following conditions to obtain a polarizing plate with a retardation layer; humidifying the polarizing plate with a retardation layer under an environment of 18°C ​​to 34°C and 60% RH to 90% RH while transporting the polarizing plate with a roll so that the weight per unit volume increases by 0.2% or more; and winding up the retardation layer-attached polarizing plate after the humidifying treatment into a roll and storing it in the rolled state for 6 hours or more. The total thickness of the polarizing plate with a retardation layer is 80 μm or less, and the ratio of the thickness of the polarizing plate to the thickness of the retardation layer (polarizing plate / retardation layer) is 5 or more. In one embodiment, the humidification time in the humidification treatment is 5 minutes or more. In one embodiment, when the polarizing plate and the retardation layer are laminated, Water Steam volume and humidification treatment Water The difference with the amount of steam is 1g / m 3 ~28g / m 3 It is. In one embodiment, the weight increase per unit volume of the retardation layer-attached polarizing plate during the humidification treatment is 2.5% or less. In one embodiment, the retardation layer or the protective layer arranged on the opposite side of the retardation layer of the polarizing plate has a moisture permeability of 300 g / m at 40° C. and 92% RH. 2 -24 hours or more. In one embodiment, the active energy ray-curable adhesive has a thickness of 0.4 μm or more after curing. In one embodiment, in the manufacturing method, the retardation layer-attached polarizing plate is transported with the retardation layer facing down in the humidification treatment. In one embodiment, the polarizing plate includes a protective layer only on the side of the polarizer opposite to the retardation layer. In one embodiment, the retardation layer is a layer in which a liquid crystal compound is aligned and fixed. In one embodiment, in the retardation layer-attached polarizing plate, the midpoint in the thickness direction of the polarizer is located closer to the retardation layer than the midpoint in the thickness direction of the retardation layer-attached polarizing plate. Effect of the Invention

[0006] According to an embodiment of the present invention, in a method for producing a polarizing plate with a retardation layer, Water A polarizing plate with a retardation layer having reduced warping can be produced simply and efficiently by laminating a polarizing plate and a retardation layer in an environment with a certain amount of steam to produce a polarizing plate with a retardation layer, subjecting the polarizing plate with a retardation layer to a specified humidification treatment, and storing the humidified polarizing plate with a retardation layer for a specified period of time. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view showing an example of a retardation layer-attached polarizing plate obtained by a production method according to an embodiment of the present invention. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing another example of a retardation layer-attached polarizing plate obtained by a manufacturing method according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0010] A. Outline of the structure of a retardation layer-attached polarizing plate obtained by the manufacturing method according to an embodiment of the present invention FIG. 1 is a schematic cross-sectional view showing an example of a retardation layer-attached polarizing plate obtained by a manufacturing method according to an embodiment of the present invention. The retardation layer-attached polarizing plate 100 in the illustrated example has a polarizing plate 10 and a retardation layer 20, typically in this order from the viewing side. In the illustrated example, the polarizing plate 10 includes a polarizer 11 and protective layers 12 and 13 on both sides of the polarizer 11. Depending on the purpose, one of the protective layers 12 and 13 may be omitted. In one embodiment, the polarizing plate 10 has a protective layer 12 only on the viewing side (opposite side to the retardation layer 20) of the polarizer 11. In practical use, a pressure-sensitive adhesive layer (not shown) is provided on the opposite side of the retardation layer 20 to the polarizing plate 10 (i.e., as the outermost layer on the opposite side to the viewing side), so that the retardation layer-attached polarizing plate can be attached to an image display cell. Furthermore, it is preferable that a release film (not shown) is temporarily attached to the surface of the pressure-sensitive adhesive layer until the retardation layer-attached polarizing plate is used. By temporarily attaching the release film, the pressure-sensitive adhesive layer is protected and the retardation layer-attached polarizing plate can be formed into a roll.

[0011] The retardation layer-attached polarizing plate has a total thickness (total thickness of the polarizing plate and the retardation layer) of 80 μm or less, preferably 70 μm or less, and more preferably 60 μm or less. The retardation layer-attached polarizing plate may have a total thickness of, for example, 25 μm or more. Furthermore, in the retardation layer-attached polarizing plate, the ratio of the thickness of the polarizing plate to the thickness of the retardation layer (polarizing plate / retardation layer: hereinafter, sometimes simply referred to as "thickness ratio") is 5 or more, preferably 5 to 16, and more preferably 5 to 14. That is, the retardation layer-attached polarizing plate applied to the manufacturing method according to the embodiment of the present invention has a small total thickness and a large ratio of the thickness of the polarizing plate to the total thickness (a small ratio of the thickness of the retardation layer). The present inventors have found that the problem of warping occurs only when the thickness and thickness ratio of the polarizing plate are within a predetermined range in the retardation layer-attached polarizing plate. More specifically, when the thickness ratio is less than 5 (the difference between the thickness of the polarizing plate and the thickness of the retardation layer is not so large) and when the thickness of the polarizing plate is excessively large, the problem of warping does not occur in the retardation layer-attached polarizing plate in many cases. The present inventors have intensively studied the suppression of warping based on such new findings, and as a result, have found that warping can be suppressed by the manufacturing method of the embodiment of the present invention (described later). Thus, the manufacturing method according to the embodiment of the present invention solves the newly recognized problem in the retardation layer-attached polarizing plate having a total thickness of 80 μm or less and a ratio of the thickness of the polarizing plate to the thickness of the retardation layer of 5 or more. In addition, in such a retardation layer-attached polarizing plate, the midpoint in the thickness direction of the polarizer is typically located closer to the retardation layer than the midpoint in the thickness direction of the retardation layer-attached polarizing plate. In addition, the thickness of the retardation layer in the ratio of the thickness of the polarizing plate to the thickness of the retardation layer means the total thickness when the retardation layer has a laminated structure of two or more layers.

[0012] In one embodiment, the moisture permeability of either the protective layer 12 or the retardation layer 20 at 40° C. and 92% RH is preferably 300 g / m 2 - 24h or more, preferably 400g / m 2 24h~1000g / m 2 24h, and more preferably 400g / m 2 24h~800g / m 2When either the protective layer 12 or the retardation layer 20 has such a moisture permeability, the effect of the humidification treatment described later becomes significant. When the moisture permeability of the retardation layer 20 is in the above range, the moisture permeability of the protective layer 12 is preferably 300 g / m 2 - 24h or less, preferably 10g / m 2 24h~150g / m 2 24h, more preferably 10g / m 2 24h~30g / m 2 In this embodiment, the protective layer 13 may be omitted in many cases.

[0013] The retardation layer 20 is typically an alignment solidified layer of a liquid crystal compound (liquid crystal alignment solidified layer). By using a liquid crystal compound, the difference between nx and ny of the resulting retardation layer can be significantly increased compared to non-liquid crystal materials, so the thickness of the retardation layer for obtaining a desired in-plane retardation can be significantly reduced. Therefore, a polarizing plate with a retardation layer can be significantly thinned. As a result, the total thickness and thickness ratio as described above can be realized. In this specification, the "alignment solidified layer" refers to a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment solidified layer obtained by hardening a liquid crystal monomer as described later. In the retardation layer 20, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the retardation layer (homogeneous alignment). The retardation layer 20 may be a single layer as shown in FIG. 1, or may have a laminated structure of two or more layers as shown in FIG. 2.

[0014] The retardation layer is attached to the polarizing plate via an active energy ray curable adhesive. When the retardation layer has a laminated structure of two or more layers, each retardation layer is attached via an active energy ray curable adhesive. The warping of a retardation layer-attached polarizing plate having the above total thickness and thickness ratio is mainly caused by shrinkage during curing of the active energy ray curable adhesive. According to the manufacturing method of the embodiment of the present invention (described later), even in a retardation layer-attached polarizing plate having the above total thickness and thickness ratio and using an active energy ray curable adhesive, warping can be suppressed well.

[0015] The retardation layer-attached polarizing plate may further include other optical functional layers. The type, characteristics, number, combination, arrangement position, etc. of the optical functional layers that can be provided in the retardation layer-attached polarizing plate may be appropriately set according to the purpose. For example, the retardation layer-attached polarizing plate may further have a conductive layer or a conductive layer-attached isotropic substrate (both are not shown). The conductive layer or the conductive layer-attached isotropic substrate is typically provided on the outside of the retardation layer 20 (opposite side to the polarizing plate 10). The conductive layer or the conductive layer-attached isotropic substrate is typically an arbitrary layer that is provided as necessary, and may be omitted. In addition, when the conductive layer or the conductive layer-attached isotropic substrate is provided, the retardation layer-attached polarizing plate may be applied to a so-called inner touch panel type input display device in which a touch sensor is incorporated between an image display cell (for example, an organic EL cell) and a polarizing plate. In addition, for example, the retardation layer-attached polarizing plate may further include other retardation layers. Other optical characteristics (for example, refractive index characteristics, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, and the like of the retardation layer can be appropriately set depending on the purpose.

[0016] Hereinafter, a method for producing the above-mentioned polarizing plate with a retardation layer according to an embodiment of the present invention will be described, and then components of the polarizing plate with a retardation layer will be described.

[0017] B. Method for manufacturing a polarizing plate with a retardation layer The method for producing a polarizing plate with a retardation layer according to an embodiment of the present invention is as follows: ,water Steam volume is 10.2g / m 3The method includes laminating a polarizing plate and a retardation layer with an active energy ray-curable adhesive while transporting the polarizing plate with a roll under the following conditions to obtain a retardation layer-attached polarizing plate; humidifying the retardation layer-attached polarizing plate while transporting the retardation layer-attached polarizing plate with a roll under an environment of 18°C ​​to 34°C and 60% RH to 90% RH so that the weight per unit volume increases by 0.2% or more; and winding up the retardation layer-attached polarizing plate after the humidifying treatment into a roll and storing it in the rolled state for 6 hours or more. Each step in the method for producing a retardation layer-attached polarizing plate will be described in order below.

[0018] B-1. Preparation of polarizing plate The polarizing plate may be produced by any suitable method. Specifically, the polarizing plate may include a polarizer produced from a single-layer resin film, or may include a polarizer produced using a laminate of two or more layers.

[0019] B-1-1. Preparation of a polarizing plate using a polarizer obtained from a single layer of resin film The method for producing a polarizer from a single-layer resin film typically includes subjecting the resin film to a dyeing treatment using a dichroic substance such as iodine or a dichroic dye, and a stretching treatment. Examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA)-based films, partially formalized PVA-based films, and partially saponified ethylene-vinyl acetate copolymer-based films. The method may further include an insolubilization treatment, a swelling treatment, a crosslinking treatment, and the like. A polarizing plate can be obtained by laminating a protective layer (protective film) on at least one side of the obtained polarizer. Such a production method is well known and commonly used in the art, and therefore a detailed description thereof will be omitted.

[0020] B-1-2. Preparation of a polarizing plate using a polarizer obtained from a laminate When a laminate is used to manufacture a polarizer, the laminate may be a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. As an example, a method for manufacturing a polarizer using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate will be described. The manufacturing method typically includes: applying a PVA-based resin solution to a resin substrate and drying the substrate to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In such a manufacturing method, the stretching typically includes immersing the laminate in an aqueous solution of boric acid to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (e.g., 95°C or higher) before stretching in the aqueous solution of boric acid. The obtained resin substrate / polarizer laminate may be used as a polarizing plate as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or a protective layer may be further laminated on the polarizer surface of the resin substrate / polarizer laminate to form a polarizing plate. Alternatively, the resin substrate may be peeled off from the resin substrate / polarizer laminate, and any suitable protective layer according to the purpose may be laminated on the peeled surface to form a polarizing plate, or a protective layer may be further laminated on the polarizer surface of the protective layer / polarizer laminate to form a polarizing plate. Details of the manufacturing method of such a polarizing plate are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.

[0021] B-2. Formation of retardation layer A method of forming the retardation layer when it is a liquid crystal alignment solidified layer will be briefly described. The liquid crystal alignment solidified layer can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted according to the purpose.

[0022] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.

[0023] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or a crosslinking treatment.

[0024] Specific examples of the liquid crystal compound and details of the method for forming the alignment solidified layer are described in JP-A-2006-163343, the disclosure of which is incorporated herein by reference.

[0025] In this manner, a liquid crystal alignment and solidified layer is formed on the substrate.

[0026] B-3. ​​Preparation of polarizing plate with retardation layer A polarizing plate with a retardation layer can be obtained by laminating the polarizing plate and the retardation layer obtained above. The polarizing plate and the retardation layer are laminated while conveying them with a roll (that is, by so-called roll-to-roll) as described above. The lamination can be typically performed by transferring a liquid crystal alignment solidified layer formed on a substrate. When the retardation layer has a laminated structure, each retardation layer may be laminated (transferred) sequentially onto the polarizing plate, or a laminate of the retardation layers may be laminated (transferred) onto the polarizing plate. The transfer is performed via an active energy ray curable adhesive. The thickness of the active energy ray curable adhesive after curing is preferably 0.4 μm or more, more preferably 0.4 μm to 3.0 μm, and even more preferably 0.6 μm to 1.5 μm. As described above, warping of a polarizing plate with a retardation layer having a specified total thickness and thickness ratio is mainly caused by shrinkage during curing of the active energy ray-curable adhesive. According to an embodiment of the present invention, warping can be effectively suppressed even in a polarizing plate with a retardation layer having a specified total thickness and thickness ratio and using an active energy ray-curable adhesive.

[0027] When the retardation layer-attached polarizing plate further includes other optically functional layers (for example, a conductive layer, another retardation layer), these optically functional layers can be laminated or formed at predetermined positions by any appropriate method.

[0028] The preparation (lamination) of polarizing plates with retardation layers is ,water Steam volume is 10.2g / m 3 The process is carried out under the following conditions: Water The steam amount is preferably 6.0 g / m 3 ~10.0g / m 3 and more preferably 8.0 g / m 3 ~9.5g / m 3 is . water By carrying out lamination under an environment in which the amount of steam is in this range, the effect of the humidification treatment described below becomes significant. Water The amount of steam can be achieved, for example, by changing the relative humidity according to the temperature in the range of 18°C ​​to 25°C. . waterThe amount of steam can be achieved, for example, by setting the relative humidity to 65% RH or less when the temperature is 18° C., or by setting the relative humidity to 55% RH or less when the temperature is 20° C., or by setting the relative humidity to 45% RH or less when the temperature is 23° C. The lower limit of the relative humidity can be, for example, 30% RH.

[0029] B-4. Humidification treatment The retardation layer-attached polarizing plate obtained above is subjected to a humidification treatment while being transported by rolls. The humidification treatment is carried out in an environment of 18° C. to 34° C. and 60% RH to 90% RH. The humidification treatment is typically carried out during the lamination process. Water Larger than the amount of steam Fresh water More specifically, the lamination is performed in an environment of a high steam content. Water Steam volume and humidification process Water The difference with the steam amount is preferably 1.0 g / m 3 ~28g / m 3 and more preferably 1.0 g / m 3 ~12g / m 3 and more preferably 1.5 g / m 3 ~10g / m 3 and particularly preferably 1.5 g / m 3 ~8g / m 3 In the humidification process Water The steam amount is preferably 10.5 g / m 3 ~30g / m 3 and more preferably 11 g / m 3 ~20g / m 3 This is the case in the humidification process. WaterThe amount of steam can be realized, for example, by setting the relative humidity to 80% RH or more when the temperature is 18°C; for example, by setting the relative humidity to 60% RH or more when the temperature is 20°C; and for example, by setting the relative humidity to 50% RH or more when the temperature is 23°C. The upper limit of the relative humidity can be, for example, 100% RH. By carrying out the humidification treatment under such conditions, an appropriate amount of moisture is imparted to the retardation layer-attached polarizing plate, and the warping of the retardation layer-attached polarizing plate having the above-mentioned predetermined thickness and thickness ratio can be suppressed. More specifically, it is as follows. The temperature and humidity conditions in the humidification treatment are close to the temperature and humidity conditions when the retardation layer-attached polarizing plate is produced, but are different from the conditions. By humidifying under such conditions, moisture can be imparted to the retardation layer-attached polarizing plate without shrinking the retardation layer-attached polarizing plate. Even if the retardation layer-attached polarizing plate is roll-transported under the same temperature and humidity conditions as when it was produced, moisture is not imparted to the retardation layer-attached polarizing plate, and no effect can be obtained. Although it is not theoretically clear, such a small difference in conditions can produce the above-mentioned unexpectedly excellent effect. On the other hand, if the amount of moisture given to the retardation layer-attached polarizing plate is too large, the warp in the reverse direction and / or the warp in the direction perpendicular to the initial direction in the plane may become large.

[0030] The humidification treatment is carried out so that the weight per unit volume of the retardation layer-attached polarizing plate increases by 0.2% or more. The weight increase per unit volume of the retardation layer-attached polarizing plate in the humidification treatment is 0.2% to 2.5%, more preferably 0.3% to 2.0%, and even more preferably 0.3% to 1.0%. The weight increase in the humidification treatment means that the retardation layer-attached polarizing plate has absorbed moisture, so by setting the weight increase amount within this range, the polarizer can absorb a desired amount of moisture. As a result, the warping of the retardation layer-attached polarizing plate can be suppressed.

[0031] The humidification time in the humidification treatment is preferably 5 minutes or more, more preferably 5 to 30 minutes, even more preferably 5 to 20 minutes, and particularly preferably 5 to 15 minutes. If the humidification time is 5 minutes or more, the desired weight gain (amount of water absorption) can be achieved. Even if the humidification time is excessively long, the effect will not change, so the upper limit of the humidification time can be determined by balancing the desired weight gain and production efficiency.

[0032] In one embodiment of the humidification treatment, the retardation layer-attached polarizing plate is transported with the retardation layer facing downward. With this configuration, it is possible to suppress appearance defects caused by foreign matter.

[0033] B-5. Roll storage The humidified polarizing plate with a retardation layer is wound into a roll and stored in the rolled state. The storage time is 6 hours or more, preferably 8 hours or more, more preferably 10 hours or more, and even more preferably 12 hours or more, as described above. The upper limit of the storage time may be, for example, 24 hours. By storing in this manner, the moisture imparted to the polarizing plate with a retardation layer by the humidification treatment can be transferred well to the polarizer. This increases the moisture content of the polarizer, and as a result, the warping of the polarizing plate with a retardation layer can be suppressed.

[0034] Typically, storage may be performed at around room temperature. The storage temperature is preferably 30° C. or lower, more preferably 20° C. to 30° C., and further preferably 23° C. to 27° C. If the storage temperature is too high, moisture imparted (absorbed) to the retardation layer-attached polarizing plate by the humidification treatment may evaporate to the outside and may not be transferred well to the polarizer.

[0035] C. Polarizing plate C-1.Polarizer As is clear from the above manufacturing method, the polarizer 11 is typically a resin film containing a dichroic material (e.g., iodine). As described above, examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA)-based films, partially formalized PVA-based films, and partially saponified ethylene-vinyl acetate copolymer-based films.

[0036] The thickness of the polarizer is preferably 15 μm or less, more preferably 1 μm to 12 μm, and further preferably 3 μm to 12 μm. When the thickness of the polarizer is within this range, the desired amount of moisture can be absorbed satisfactorily by the above-mentioned humidification treatment.

[0037] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 42.0% to 46.0%, and preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0038] C-2.Protective layer The protective layer 12 and the protective layer 13 are each formed of any appropriate film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the films include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Preferably, the protective layer 12 and the protective layer 13 are each formed of TAC. With such a configuration, the effects of the embodiment of the present invention can be significant.

[0039] The retardation layer-attached polarizing plate obtained by the manufacturing method of the embodiment of the present invention is typically placed on the viewing side of an image display device, and the protective layer 12 is typically placed on the viewing side. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary. In addition, the protective layer 12 may be subjected to treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarization function or imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the retardation layer-attached polarizing plate can be suitably applied to image display devices that can be used outdoors.

[0040] The thickness of the protective layer 12 is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 15 μm to 35 μm. When a surface treatment is applied, the thickness of the protective layer 12 includes the thickness of the surface treatment layer.

[0041] In one embodiment, the protective layer 13 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm. The thickness of the protective layer 13 is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 10 μm to 30 μm.

[0042] D. Retardation layer As described above, the retardation layer 20 may be a single layer or may have a laminated structure of two or more layers.

[0043] When the retardation layer 20 is a single layer, the retardation layer may function as a λ / 4 plate in one embodiment. Specifically, the Re(550) of the retardation layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and further preferably 110 nm to 160 nm. The thickness of the retardation layer may be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. When the retardation layer is a liquid crystal alignment solidified layer, the thickness may be, for example, 1.0 μm to 2.5 μm. In this embodiment, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and further preferably 44° to 46°. In this embodiment, the retardation layer-attached polarizing plate may further have a retardation layer (not shown) between the retardation layer 20 and the pressure-sensitive adhesive layer 30, the retardation layer having a refractive index characteristic of nz>nx=ny. When the retardation layer is a single layer, the retardation layer preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light.

[0044] In another embodiment, the retardation layer may function as a λ / 2 plate. Specifically, the Re(550) of the retardation layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and further preferably 230 nm to 280 nm. The thickness of the retardation layer may be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate. When the retardation layer is a liquid crystal alignment solidified layer, the thickness may be, for example, 2.0 μm to 4.0 μm. In this embodiment, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably 12° to 16°.

[0045] When the retardation layer 20 has a laminated structure, the retardation layer typically has a two-layer structure of an H layer 21 and a Q layer 22 in this order from the polarizing plate side, as shown in FIG. 2. The H layer typically functions as a λ / 2 plate, and the Q layer typically functions as a λ / 4 plate. Specifically, the Re(550) of the H layer is preferably 200 nm to 300 nm, more preferably 220 nm to 290 nm, and further preferably 230 nm to 280 nm; the Re(550) of the Q layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and further preferably 110 nm to 150 nm. The thickness of the H layer can be adjusted so that a desired in-plane retardation of the λ / 2 plate is obtained. When the H layer is a liquid crystal alignment solidified layer, the thickness can be, for example, 2.0 μm to 4.0 μm. The thickness of the Q layer can be adjusted so that a desired in-plane retardation of the λ / 4 plate is obtained. When the Q layer is a liquid crystal alignment solidified layer, its thickness may be, for example, 1.0 μm to 2.5 μm. In this embodiment, the angle between the slow axis of the H layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 12° to 16°; the angle between the slow axis of the Q layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 72° to 76°. The order of arrangement of the H layer and the Q layer may be reversed, and the angle between the slow axis of the H layer and the absorption axis of the polarizer and the angle between the slow axis of the Q layer and the absorption axis of the polarizer may be reversed. When the retardation layer has a laminated structure, each layer (e.g., the H layer and the Q layer) may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the retardation value changes very little depending on the wavelength of the measurement light.

[0046] The retardation layer (each layer in the case of a laminated structure) typically exhibits a refractive index characteristic relationship of nx > ny = nz. Note that "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3.

[0047] The retardation layer is typically a liquid crystal alignment solidified layer as described above. Examples of the liquid crystal compound include a liquid crystal compound (nematic liquid crystal) whose liquid crystal phase is a nematic phase. As such a liquid crystal compound, for example, a liquid crystal polymer or a liquid crystal monomer can be used. The mechanism for the expression of liquid crystallinity of the liquid crystal compound may be either lyotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination.

[0048] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the alignment state of the liquid crystal monomer can be fixed by polymerizing or crosslinking (i.e., curing) the liquid crystal monomer. After aligning the liquid crystal monomer, for example, by polymerizing or crosslinking the liquid crystal monomers with each other, the above alignment state can be fixed. Here, a polymer is formed by polymerization and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystalline. Therefore, in the formed retardation layer, for example, a transition from a liquid crystal phase, a glass phase, or a crystal phase due to a temperature change peculiar to the liquid crystalline compound does not occur. As a result, the retardation layer becomes an extremely stable retardation layer that is not affected by temperature changes.

[0049] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its type. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0050] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. For example, nematic liquid crystal monomers are preferred as the liquid crystal monomer. EXAMPLES

[0051] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified. (1) Thickness The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). (2) Warpage The retardation layer-attached polarizing plates obtained in the Examples and Comparative Examples were cut into a size of 140 mm x 70 mm before and after humidification and storage. The polarizing plates were cut so that the absorption axis direction of the polarizer was the long side direction. The cut retardation layer-attached polarizing plates were placed on a flat surface, and the height of the highest part from the flat surface was taken as the warpage. Next, the cut polarizing plate with a retardation layer was left for 24 hours in an environment of 23° C. and 55% RH, and the amount of warping after that was measured in the same manner as above, and the change in the amount of warping before and after leaving it was evaluated according to the following criteria. ○: Change in warpage is within ±5mm ×: The change in the amount of warping is greater than ±5 mm. In addition, if the warp is convex toward the resting surface, it is represented as "positive (+)", and if it is convex toward the opposite side to the resting surface, it is represented as "negative (-)".

[0052] [Example 1] 1. Preparation of Polarizing Plates A long roll of a 30 μm thick PVA resin film was uniaxially stretched in the long direction by a roll stretching machine so that the total stretch ratio was 6.0 times, while simultaneously undergoing swelling, dyeing, crosslinking and washing treatments, and finally drying treatment to produce a polarizer with a thickness of 12 μm. An HC-TAC film was attached to one surface of the obtained polarizer as a viewing side protective layer via a PVA adhesive. The HC-TAC film is a film in which a hard coat (HC) layer (thickness 7 μm) is formed on a TAC film (thickness 25 μm), and the TAC film was attached to the polarizer side. Furthermore, a TAC film (thickness 25 μm) was attached to the other surface of the polarizer via a PVA adhesive to obtain a polarizing plate having a configuration of protective layer (HC-TAC film) / polarizer / protective layer (TAC film).

[0053] 2. Preparation of polarizing plate with retardation layer 2-1. Preparation of retardation layer A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. [ka] The surface of a polyethylene terephthalate (PET) film (thickness 38 μm) was rubbed with a rubbing cloth and subjected to an alignment treatment. The direction of the alignment treatment was set to be 15° from the viewing side with respect to the direction of the absorption axis of the polarizer when it was attached to the polarizing plate. The above liquid crystal coating liquid was applied to this alignment-treated surface with a bar coater, and the liquid crystal compound was aligned by heating and drying at 90°C for 2 minutes. The liquid crystal layer thus formed was then irradiated with 1 mJ / cm using a metal halide lamp.2 The liquid crystal layer was cured by irradiating the liquid crystal with light, forming a liquid crystal alignment solidified layer A on the PET film. The liquid crystal alignment solidified layer A had a thickness of 2.0 μm and an in-plane retardation Re(550) of 270 nm. Furthermore, the liquid crystal alignment solidified layer A exhibited a refractive index characteristic of nx>ny=nz. The liquid crystal alignment solidified layer A was used as the H layer. A liquid crystal alignment layer B was formed on a PET film in the same manner as above, except that the coating thickness was changed and the orientation treatment direction was set to be 75° from the viewing side relative to the absorption axis direction of the polarizer. The liquid crystal alignment layer B had a thickness of 1.0 μm and an in-plane retardation Re(550) of 140 nm. Furthermore, the liquid crystal alignment layer B showed a refractive index characteristic of nx>ny=nz. The liquid crystal alignment layer B was used as the Q layer.

[0054] 2-2. Preparation of polarizing plate with retardation layer The liquid crystal alignment solidified layer A (H layer) and the liquid crystal alignment solidified layer B (Q layer) obtained in 2-1 above were transferred in this order onto the TAC film surface of the polarizing plate obtained in 1 above. At this time, the transfer (lamination) was performed so that the angle between the absorption axis of the polarizer and the slow axis of the alignment solidified layer A was 15°, and the angle between the absorption axis of the polarizer and the slow axis of the alignment solidified layer B was 75°. Note that each transfer (lamination) was performed via an ultraviolet-curing adhesive (thickness 1.0 μm). In this way, a retardation layer-attached polarizing plate having a configuration of protective layer / adhesive / polarizer / adhesive / protective layer / adhesive layer / retardation layer (H layer) / adhesive layer / retardation layer (Q layer) was obtained. The total thickness of the retardation layer-attached polarizing plate was 76 μm, and the thickness ratio was 14. Note that the transfer (lamination) was performed while transporting with a roll. Furthermore, the transfer (lamination) was performed with a UV-curing adhesive (thickness 1.0 μm). ,water Steam volume 9.3g / m 3 The experiment was carried out under the following conditions: 23°C and 45% RH.

[0055] 3. Moisture treatment and roll storage The retardation layer-attached polarizing plate obtained in the above 2 was subjected to a humidification treatment while being transported by rolls. The humidification treatment was performed at 23° C. and 80% RH. (water Steam volume 16.5g / m 3) for 10 minutes. The humidified polarizing plate with a retardation layer was wound into a roll, and the roll was stored at 23°C and 55% RH for 12 hours. The polarizing plates with a retardation layer before the humidification treatment and after the roll storage were each subjected to the evaluation of (2) above. The results are shown in Table 1.

[0056] [Example 2] 1. Preparation of Polarizing Plates As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, and a polarizing plate having a resin substrate / polarizer structure was obtained.

[0057] Furthermore, an HC-COP film was attached as a viewing-side protective layer to the surface of the obtained polarizer (the surface opposite to the resin substrate) via an ultraviolet-curing adhesive. The HC-COP film is a film in which an HC layer (thickness 2 μm) is formed on a cycloolefin resin (COP) film (thickness 25 μm), and the COP film was attached to the polarizer side. Next, the resin substrate was peeled off to obtain a polarizing plate having a configuration of HC-COP film (viewing-side protective layer) / polarizer.

[0058] 2. Preparation of polarizing plate with retardation layer A polarizing plate with a retardation layer having a structure of protective layer / adhesive / polarizer / adhesive layer / retardation layer (H layer) / adhesive layer / retardation layer (Q layer) was obtained in the same manner as in Example 1, except that the polarizing plate obtained in 1 above was used. The total thickness of the polarizing plate with a retardation layer was 38 μm, and the thickness ratio was 7.

[0059] 3. Moisture treatment and roll storage The retardation layer-attached polarizing plate obtained in the above 2 was subjected to a humidification treatment while being transported by rolls. The humidification treatment was performed at 23° C. and 60% RH. (water Steam volume 12.4g / m 3) for 10 minutes. The humidified polarizing plate with a retardation layer was wound into a roll, and the roll was stored in the same manner as in Example 1. The polarizing plates with a retardation layer before the humidification treatment and after the roll storage were each subjected to the evaluation of (2) above. The results are shown in Table 1.

[0060] [Example 3] A retardation layer-attached polarizing plate having a structure of protective layer / adhesive / polarizer / adhesive layer / retardation layer (H layer) was obtained in the same manner as in Example 2, except that the retardation layer (Q layer) was not provided. The total thickness of the retardation layer-attached polarizing plate was 36 μm, and the thickness ratio was 13. The obtained retardation layer-attached polarizing plate was subjected to a humidification treatment in the same manner as in Example 2, and after the humidification treatment, it was wound into a roll and stored in the same manner as in Example 1. The retardation layer-attached polarizing plate before the humidification treatment and after the roll storage were each subjected to the above evaluation (2). The results are shown in Table 1.

[0061] [Comparative Example 1] The same retardation layer-attached polarizing plate as in Example 2 was subjected to a humidification treatment while being transported by rolls. The humidification treatment was performed at 23° C. and 45% RH. (water Steam volume 9.3g / m 3 ) for 10 minutes. The humidified polarizing plate with a retardation layer was wound into a roll, and the roll was stored in the same manner as in Example 1. The polarizing plates with a retardation layer before the humidification treatment and after the roll storage were each subjected to the evaluation of (2) above. The results are shown in Table 1.

[0062] [Comparative Example 2] The same retardation layer-attached polarizing plate as in Example 2 was subjected to a humidification treatment while being transported by rolls. The humidification treatment was performed at 60° C. and 60% RH. (water Steam volume: 77.9g / m 3 ) for 10 minutes. The humidified polarizing plate with a retardation layer was wound into a roll, and the roll was stored in the same manner as in Example 1. The polarizing plates with a retardation layer before the humidification treatment and after the roll storage were each subjected to the evaluation of (2) above. The results are shown in Table 1.

[0063] [Comparative Example 3] The same retardation layer-attached polarizing plate as in Example 2 was subjected to a humidification treatment while being transported by rolls. The humidification treatment was performed at 40° C. and 60% RH. (water Steam volume: 30.7g / m 3 ) for 10 minutes. The humidified polarizing plate with a retardation layer was wound into a roll, and the roll was stored in the same manner as in Example 1. The polarizing plates with a retardation layer before the humidification treatment and after the roll storage were each subjected to the evaluation of (2) above. The results are shown in Table 1.

[0064] [Comparative Example 4] A polarizing plate with a retardation layer was prepared in the same manner as in Example 2, and wound up in a roll as it was. The roll was subjected to a humidification treatment at 23°C and 60% RH for 10 minutes in the same manner as in Example 2, and then stored in the same manner as in Example 1. The polarizing plates with a retardation layer before the humidification treatment and after the roll storage were each subjected to the evaluation of (2) above. The results are shown in Table 1. In Table 1, "inside the roll" refers to the portion of the roll excluding the outer three turns (the outer three turns can be discarded). Since the moisture caused by the humidification treatment is substantially all absorbed in the outer three turns, the weight inside the roll does not change.

[0065] [Reference example 1] A polarizer having a thickness of 22 μm was prepared in the same manner as in Example 1, except that a PVA-based resin film having a thickness of 60 μm was used. A TAC film (thickness 71 μm) with an HC layer was attached to one surface of the obtained polarizer. Furthermore, a polycarbonate resin retardation film (thickness 58 μm) showing reverse dispersion wavelength dependency and having Re (550) of 140 nm was attached to the other surface of the polarizer. Here, the retardation film was attached so that the angle between the slow axis of the retardation film and the absorption axis of the polarizer was 45°. In this way, a polarizing plate with a retardation layer was obtained. The total thickness of the polarizing plate with a retardation layer was 151 μm, and the thickness ratio was 1.6. This polarizing plate with a retardation layer was cut into a size of 140 mm × 70 mm and placed on a flat surface, and no warping was observed.

[0066] [Reference example 2] A polarizer having a thickness of 22 μm was produced in the same manner as in Reference Example 1. A TAC film with an HC layer (thickness 91 μm) was attached to one surface of the obtained polarizer, and a TAC film (thickness 80 μm) was attached to the other surface to obtain a polarizing plate. A polarizing plate with a retardation layer having a structure of a TAC film with an HC layer / polarizer / TAC film / adhesive layer / retardation layer (H layer) / adhesive layer / retardation layer (Q layer) was obtained in the same manner as in Example 1, except that this polarizing plate was used. The total thickness of the polarizing plate with a retardation layer was 198 μm, and the thickness ratio was 39. This polarizing plate with a retardation layer was cut into a size of 140 mm×70 mm and placed on a flat surface, and no warping was observed.

[0067] [Table 1]

[0068] [evaluation] As is clear from Table 1, the retardation layer-attached polarizing plate obtained in the examples of the present invention is significantly suppressed in both warping at the time of cutting and change in warping over time by carrying out a specified humidification treatment and storing in a roll. Furthermore, as is clear from the reference examples, such warping is a problem specific to retardation layer-attached polarizing plates that are thin in total thickness and have a large ratio of the polarizing plate thickness to the total thickness. [Industrial Applicability]

[0069] The retardation layer-attached polarizing plate obtained by the manufacturing method of the embodiment of the present invention is used as a retardation layer-attached polarizing plate for an image display device, and can be suitably used in a curved, bent, foldable, or rollable image display device (typically, a resin substrate is used as the substrate in such an image display device). Typical examples of the image display device include a liquid crystal display device, an organic EL display device, and an inorganic EL display device. [Explanation of symbols]

[0070] 10 Polarizing plate 11 Polarizer 12 Protective layer 13. Protective layer 20-bit phase difference layer 21 Phase difference layer (H layer) 22 Phase difference layer (Q layer) 100 Phase Difference Layered Polarizing Plate 102 Phase difference layer polarizing plate

Claims

1. A method for producing a polarizing plate with a retardation layer, the polarizing plate including a polarizer and a protective layer on at least one of the polarizers, and a retardation layer, comprising: Water vapor content is 10.2 g / m 3 Under the following environment, a polarizing plate and a retardation layer are laminated with an active energy ray-curable adhesive therebetween while being transported by rolls to obtain a polarizing plate with a retardation layer; While transporting the retardation layer-attached polarizing plate by rolls, the retardation layer-attached polarizing plate is subjected to a humidification treatment in an environment having a water vapor amount larger than that during lamination of the polarizing plate and the retardation layer, and in an environment of 18° C. to 34° C. and 60% RH to 90% RH, so that the weight per unit volume increases by 0.2% to 2.5%; and The retardation layer-attached polarizing plate after the humidification treatment is wound into a roll and stored in the rolled state for 6 hours or more; Including, the total thickness of the polarizing plate with a retardation layer is 80 μm or less, and the ratio of the thickness of the polarizing plate to the thickness of the retardation layer (polarizing plate / retardation layer) is 5 or more; Manufacturing method.

2. The method for producing a polarizing plate with a retardation layer according to claim 1 , wherein the humidification time in the humidification treatment is 5 minutes or more.

3. The difference between the amount of water vapor when the polarizing plate and the retardation layer are laminated and the amount of water vapor when the humidification treatment is performed is 1 g / m 3 ~28g / m 3 The method for producing a polarizing plate with a retardation layer according to claim 1 or 2,

4. The retardation layer or the protective layer disposed on the opposite side of the retardation layer of the polarizing plate has a moisture permeability of 300 g / m at 40° C. and 92% RH. 2 The method for producing a polarizing plate with a retardation layer according to any one of claims 1 to 3, wherein the retardation period is 24 hours or more.

5. The method for producing a polarizing plate with a retardation layer according to claim 1 , wherein the active energy ray-curable adhesive has a thickness of 0.4 μm or more after curing.

6. The method for producing a polarizing plate with a retardation layer according to claim 1 , wherein the retardation layer-attached polarizing plate is transported with the retardation layer facing down in the humidification treatment.

7. The method for producing a polarizing plate with a retardation layer according to claim 1 , wherein the polarizing plate includes a protective layer only on the side of the polarizer opposite to the retardation layer.

8. The method for producing a polarizing plate with a retardation layer according to claim 1 , wherein the retardation layer is a layer in which a liquid crystal compound is aligned and solidified.

9. 9. The method for producing a polarizing plate with a retardation layer according to claim 1, wherein in the polarizing plate with a retardation layer, a midpoint in the thickness direction of the polarizer is located closer to the retardation layer than a midpoint in the thickness direction of the polarizing plate with a retardation layer.

Citation Information

Patent Citations

  • Manufacturing method of polarizing element, polarizing element, and projector

    JP2008015145A

  • Liquid crystal display device

    JP2012137723A

  • Method of manufacturing optical laminate and method of manufacturing optical laminate with adhesive layers

    JP2019159200A

  • Retardation film and optical device using the same

    JP3325560B2

  • Polarizing plate, liquid crystal display device

    WO2015111474A1